The injection of Ghrelin (OXE-103) improves subacute concussion symptom burden and quality of life - Rippee, Michael; Wyand, Michael; Chen, Jamie; Kirchhoff-Rowald, Amelia; Hunt, Suzanne; Bansal, Vishal (Archives of physical medicine and rehabilitation, 2024)
To investigate the benefit of Ghrelin (OXE-103) for treating subacute concussion. Open-label treatment arm (OXE-103) with a non-treatment concurrent control arm receiving standard of care. Tertiary referral center outpatient concussion clinic. Men and women, ages 18-60 years old, with a documented concussion. Enrollment within 28 days of injury and a symptom severity score of 20 or more using the Post-Concussion Symptom Score (PCSS). Eligible patients were approached to enroll in treatment arm, if they declined, were subsequently approached to enroll in control arm. A total of 19 subjects enrolled; 13 treatment and 6 control. Ghrelin (OXE-103) 40ug/kg SC twice daily by self-injection for 14 days. Questionnaires (PCSS, QOLIBRI) obtained at specified intervals through day 44. Change in Post-Concussion Symptom Score, Quality of Life after Brain Injury scale (QOLIBRI); 20% improvement on either was considered a responder. Median decrease in PCSS score change from baseline following treatment for non-ghrelin -1 (IQR –14, 1) at day 15 and –7 (IQR –22, 16) at day 44 vs ghrelin -21 (IQR –30, -6) at day 15 and –34 (IQR –44, -24) at day 44. Median change of QOLIBRI scores from baseline following treatment for non-ghrelin 1 (IQR –4, 6) at day 15 and 1 (IQR –6, 5) at day 44 vs ghrelin 2 (IQR 1, 6) at day 15 and 5 (IQR 3, 12) at day 44. Percent responders (20% improvement) at day 44 on PCSS was 85% in ghrelin arm vs 33% in non-ghrelin arm. Percent responder (20% improvement) at day 44 on QOLIBRI was 85% in ghrelin arm vs 33% in non-ghrelin arm. Exogenous ghrelin improved PCSS scores and QOLIBRI compared to those receiving only standard therapy. We recognize the limitations of this study, including small sample size and the lack of pure randomization. The results from this study indicate that ghrelin therapy is a promising and potential therapeutic to treat post-concussion patients suffering from ongoing symptom burdens. A larger, multi-center randomized trial would be an important next step to confirm the signal observed in this open label study. Dr. Bansal is CSO and Dr. Wyand CEO of Oxeia Biopharmaceuticals-Boston, MA